Musculoskeletal adverse events induced by immune checkpoint inhibitors: a large-scale pharmacovigilance study - Liu, Hao; Li, Yumin; Li, Jie; Zhang, Qiongchi; Wu, Jingtao; Li, Xinyu; Meng, Liesu; Cao, Shuai; Li, Haopeng (Frontiers in Pharmacology, 2023)
Abstract Background: The musculoskeletal toxicity of immune checkpoint inhibitors (ICIs) is receiving increasing attention with clinical experience. Nevertheless, the absence of a systematic investigation into the musculoskeletal toxicity profile of ICIs currently results in the under-recognition of associated adverse events. Further and more comprehensive investigations are warranted to delineate the musculoskeletal toxicity profile of ICIs and characterize these adverse events. Material and methods: The present study employed the FDA Adverse Event Reporting System database to collect adverse events between January 2010 and March 2021. We utilized both the reporting odds ratio and the Bayesian confidence propagation neural network algorithms to identify suspected musculoskeletal adverse events induced by ICIs. Subsequently, the clinical characteristics and comorbidities of the major musculoskeletal adverse events were analyzed. The risk of causing these events with combination therapy versus monotherapy was compared using logistic regression model and Ω shrinkage measure model. Results: The musculoskeletal toxicity induced by ICIs primarily involves muscle tissue, including neuromuscular junctions, fascia, tendons, and tendon sheaths, as well as joints, spine, and bones, including cartilage. The toxicity profile of PD-1/PD-L1 and CTLA-4 inhibitors varies, wherein the PD-1 inhibitor pembrolizumab exhibits a heightened overall risk of inducing musculoskeletal adverse events. The major ICIs-induce musculoskeletal adverse events, encompassing conditions such as myositis, neuromyopathy (including myasthenia gravis, Lambert-Eaton myasthenic syndrome, Guillain-Barré syndrome, and Chronic inflammatory demyelinating polyradiculoneuropathy), arthritis, fractures, myelitis, spinal stenosis, Sjogren's syndrome, fasciitis, tenosynovitis, rhabdomyolysis, rheumatoid myalgia, and chondrocalcinosis. Our study provides clinical characteristics and comorbidities of the major ICIs-induced musculoskeletal adverse events. Furthermore, the combination therapy of nivolumab and ipilimumab does not result in a statistically significant escalation of the risk associated with the major musculoskeletal adverse events. Conclusion: Immune checkpoint inhibitors administration triggers a range of musculoskeletal adverse events, warranting the optimization of their management during clinical practice.